Tissue-Specific Autoantibodies Improve Diagnosis of Primary Sjögren’s Syndrome in the Early Stage and Indicate Localized Salivary Injury - Yuebo Jin; Jing Li; Jiali Chen; Miao Shao; Ruijun Zhang; Yichen Liang; Xia Zhang; Xiaoying Zhang; Qin Zhang; Fangting Li; Yaobin Cheng; Xiaolin Sun; et al. (Journal of Immunology Research)
Primary Sjögren’s syndrome (pSS) is a chronic autoimmune disease characterized by lymphocytic infiltration of exocrine glands. Due to the absence of specific clinical manifestations and biomarkers in the early stage, pSS is generally underrecognized. To elucidate the role of the tissue-specific autoantibodies (TSAs), i.e., anti-CA6, anti-SP1, and anti-PSP antibodies, we enrolled 137 pSS patients, 32 secondary Sjögren’s syndrome (sSS) patients, and 127 healthy controls (HCs), whose serum and saliva samples were collected. TSA levels were detected by ELISA, and the clinical and laboratory data was reviewed from the medical records. The analysis results showed the following: (1) Compared to HCs, the serum IgA levels of anti-CA6, anti-SP1 and anti-PSP were significantly higher in pSS as well as in sSS patients, and anti-CA6 IgG was also notably higher in pSS patients. (2) The positivity of anti-CA6, anti-PSP and all the three antibodies together were significantly increased in anti-SSA-negative pSS patients. (3) The average IgM levels of anti-CA6 and anti-SP1 decreased as the disease duration extended. (4) The anti-CA6-positive patients have significantly higher levels of serum IgA, while the anti-PSP-positive group has a notably higher serum IgM level. (5) Another autoantibody specific to the salivary glands, anti-α-fodrin antibody, was elevated in TSA-positive patients, especially in the anti-CA6-positive group. (6) Preliminary detection of saliva TSAs showed that all the IgG levels of these three antibodies increased significantly in pSS patients. In conclusion, TSAs improve diagnosis of pSS in the early stage, especially in anti-SSA-negative patients, and their tissue-specific nature indicates localized salivary injury, which deserves further studies to clarify the mechanism.